Situational Judgment and Job Performance - CHAN, David (Institutional Knowledge at Singapore Management University, 2002)
Data from 160 civil service employees demonstrate the validity of a situational judgment test in predicting overall job performance as well as three performance dimensions: task performance (core technical proficiency), motivational contextual performance (job dedication), and interpersonal contextual performance (interpersonal facilitation). Situational judgment also provided incremental validity over the prediction provided jointly by cognitive ability, the Big Five personality traits, and job experience. These findings extended the work of Clevenger, Pereira, Wiechmann, SCHMITT, and Harvey (2001) on the incremental validity of situational judgment tests as well as the meta-analytic results reported by McDaniel, Morgeson, Finnegan, Campion, and Braverman (2001). Implications are discussed in terms of research on the prediction and understanding of job performance.